WALLABY pre-pilot survey: H i content of the Eridanus supergroup. Issue 2 (9th August 2021) - For, B-Q; Wang, J; Westmeier, T; Wong, O I; Murugeshan, C; Staveley-Smith, L; Courtois, H M; Pomarède, D; Spekkens, K; Catinella, B; McQuinn, K B W; Elagali, A; et al.
ABSTRACT: We present observations of the Eridanus supergroup obtained with the Australian Square Kilometre Array Pathfinder (ASKAP) as part of the pre-pilot survey for the Widefield ASKAP L-band Legacy All-sky Blind surveY (WALLABY). The total number of detected H i sources is 55, of which 12 are background galaxies not associated with the Eridanus supergroup. Two massive H i clouds are identified and large H i debris fields are seen in the NGC 1359 interacting galaxy pair, and the face-on spiral galaxy NGC 1385. We describe the data products from the source finding algorithm and present the basic parameters. The presence of distorted H i morphology in all detected galaxies suggests ongoing tidal interactions within the subgroups. The Eridanus group has a large fraction of H i -deficient galaxies as compared to previously studied galaxy groups. These H i -deficient galaxies are not found at the centre of the group. We find that galaxies in the Eridanus supergroup do not follow the general trend of the atomic gas fraction versus stellar mass scaling relation, which indicates that the scaling relation changes with environmental density. In general, the majority of these galaxies are actively forming stars.